“Toward a Shamanic Daily Life”: The Response of a Japanese Spiritual Therapist to COVID-19 - Rivadossi, Silvia (Journal of Religion in Japan, 2022)
This article contributes to the discussion on reactions and responses to the coronavirus pandemic in Japan, with specific reference to the field of “new spirituality” and, within this broad category, of shamanic spirituality. The case of the dance therapist, or “dance movement shaman,” Ms. Hiroda demonstrates how she managed to keep in contact with her practitioners and to design new ways to help them cope with the situation. The solution she offers, in line with the characteristics of shamanic spirituality, is to help each individual to acknowledge the importance of interconnectedness. In particular, Ms. Hiroda emphasizes body, community, and nature: to become aware of one’s own body again and of the necessity of connection with others and nature, especially in times of interpersonal distancing and crisis. Her response to the first wave of COVID-19 is thus to offer a strategy to live peacefully with—and despite—the virus.